VWCE Functions as a Tumor Suppressor in Breast Cancer Cells - Zhang, Dan; Wan, Lili; Yang, Fan; Liu, Wenlan; Liu, Litao; He, Shengnan; Xie, Ni (Frontiers in Oncology, 2020)
Breast cancer remains a leading cause of cancer-related death, for which the majority of deaths result from metastases. Von Willebrand factor C and EGF domain (VWCE) is a member of the Von Willebrand factor (VWF) gene family; however, its function, regulatory mechanism, and clinical value in breast cancer remain unclear. In the present study, we sought to elucidate the role of VWCE in breast cancer metastasis. We examined the expression of VWCE in breast cancer tissues and normal control tissues of 50 breast cancer patients. We found that VWCE expression was downregulated in breast cancer cells and tissues compared to normal breast epithelial cells or the adjacent normal tissues. To explore the role of VWCE in human breast cancer development, we introduced a VWCE-overexpressing or control lentiviral vector into the breast cancer MDA-MB-453 and MDA-MB-231 lines in vitro. The overexpression of VWCE inhibited the proliferation, migration, invasion, and chemoresistance of the breast cancer cell lines. More importantly, the forced expression of VWCE suppressed tumor formation and metastasis in nude mice. iTRAQ-based quantitative proteomic analysis revealed that VWCE overexpression induced a 10-fold decrease in the level of WD-repeat domain 1 (WDR1) protein expression. Rescue experiments further verified that WDR1 was a downstream molecule of VWCE, and WDR1 overexpression reversed the above effects of VWCE overexpression on tumor growth. Therefore, VWCE may represent a novel tumor suppressor, for which its deregulation promotes breast cancer progression via the upregulation of WDR1.